On Analytical Solutions of Some Types of Ordinary Differential Difference Equations (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
We studied in this work the applicability of Laplace decomposition method (LDM) and modified Laplacedecomposition method (MLDM) of differential-difference equations of order (2,1), which means the differential equation is oforder 2 and the difference equation is of order 1. Finally, we give two illustrative examples to show the applicability and theeffectiveness of the methods above